The roads towards complex water governance: The Colombian case study - Distefano, T.; Isaza, A. S.; Morlin, G. S.; Carmona, V. P.; Palacio, C. I. V.; Arango-Aramburo, S. (Elsevier, 2025)
This research employs the principles of Post-Normal Science (PNS) and Systems of Systems (SoS) methodologies to extend the scope of the virtual water concept by incorporating numerous socioeconomic variables, including political factors, within the context of Colombia. Through a combination of qualitative and quantitative analyses, the study utilizes causal loop diagrams to explore complex dynamics and feedback effects within and across the ecological, social, and economic systems. The analysis is undertaken at a low spatial scale, by focusing on administrative departments, thereby capturing the geographical and socioeconomic heterogeneity and relationships existing within the national borders. Furthermore, it considers the influence of the peace agreement, ratified in 2016, on deforestation and, then, on water governance. By spotlighting deforestation and its consequences on water availability as a prominent case study, this investigation underscores the necessity of incorporating diverse complex relationships in addressing water governance challenges. This study offers a comprehensive framework to support policy interventions in Colombia and similar contexts, ultimately advocating for a holistic approach that addresses the diverse dynamics at play.